Tinjauan Pustaka Sistematis: Kemampuan Pemecahan Masalah Matematika Ditinjau dari Kecerdasan Emosional - I Kadek Wisnu Nata; Ni Ketut Suarni; I Gede Margunayasa (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Emotional intelligence is a central aspect in improving math problem solving skills. Through the problem solving skills possessed by students, students are able to solve complex problems and are able to deal with problems in everyday life well. This research aims to conduct a literature review related to emotional intelligence in terms of student learning motivation. This research method used in this research is SLR (Systematic Literature Review). Data collection is done by identifying or reviewing all articles that have the same research topic in this study. The articles used in this study totaled 27 national and international journal articles obtained from garuda, google scholar, sinta and reseachgate. From this study, it was found that emotional intelligence has an important role in math problem solving ability. Students with high emotional intelligence and high mathematical ability are able to solve the given problem correctly and can gather information that can help solve the problem.